Numerical modelling of the RF plasma production in URAGAN-2М stellarator with crankshaft antenna - Moiseenko, V.Е.; Stadnik, Yu.S.; Volkov, E.D.; Schvets, O.M. (Вопросы атомной науки и техники, 2006)
The qualitative technique of the analysis of the efficiency of the RF plasma production is presented in which the solution of boundary problem for Maxwell’s equations is only necessary. The analysis of the character of the plasma production process with the crankshaft antenna in Uragan-2M stellarator is carried out. The discussion of the calculations results is presented.